2018
DOI: 10.3389/fpls.2018.00272
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene-Related Gene Expression Networks in Wood Formation

Abstract: Thickening of tree stems is the result of secondary growth, accomplished by the meristematic activity of the vascular cambium. Secondary growth of the stem entails developmental cascades resulting in the formation of secondary phloem outwards and secondary xylem (i.e., wood) inwards of the stem. Signaling and transcriptional reprogramming by the phytohormone ethylene modifies cambial growth and cell differentiation, but the molecular link between ethylene and secondary growth remains unknown. We addressed this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 79 publications
0
28
0
Order By: Relevance
“… Liu et al (2017) reported that Populus ERF type TF, PsnSHN2 , is predominantly expressed in xylem tissues, and that it positively regulates cellulose and hemicellulose biosynthesis but negatively regulates lignin biosynthesis. Recently, Seyfferth et al (2018) constructed an ethylene-related gene expression network during SCW formation, ETHYLENE INSENSITIVE 3D ( EIN3D ) and 11 ERFs were identified as hub genes. Interestingly, a VNI2 homolog is highly associated with EIN3D , suggesting EIN3D may act upstream or together with VIN2 during SCW formation.…”
Section: Ethylene Related Tfs In Scw Biosynthesismentioning
confidence: 99%
“… Liu et al (2017) reported that Populus ERF type TF, PsnSHN2 , is predominantly expressed in xylem tissues, and that it positively regulates cellulose and hemicellulose biosynthesis but negatively regulates lignin biosynthesis. Recently, Seyfferth et al (2018) constructed an ethylene-related gene expression network during SCW formation, ETHYLENE INSENSITIVE 3D ( EIN3D ) and 11 ERFs were identified as hub genes. Interestingly, a VNI2 homolog is highly associated with EIN3D , suggesting EIN3D may act upstream or together with VIN2 during SCW formation.…”
Section: Ethylene Related Tfs In Scw Biosynthesismentioning
confidence: 99%
“…The APETALA2/ethylene response factors (AP2/ERFs) are TFs that have been frequently implicated in regulation of xylem differentiation and wood formation but that are functionally poorly described (Seyfferth et al ., ). Evidence is accumulating, however, that AP2/ERF TFs may play a role in lignin biosynthesis (Ambavaram et al ., ; Vahala et al ., ; Taylor‐Teeples et al ., ; Lee et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Of these, PtNAC156, PtBLH3 and PtMYB128 were associated with PtGT43B, but not with PtGT43C (Figure 4a). PtGT43B was also uniquely co-expressed with an ethylene response factor (ERF) transcription factor PtERF119 homologous to AtSHINE3 (AtSHN3), which was recently found as an important hub transcription factor in secondary wall forming aspen xylem (Seyfferth et al, 2018). Overexpression of the closely related Populus SHN2/ERF118 gene induced cellulose and hemicellulose and suppressed lignin biosynthesis in Nicotiana tabacum (tobacco; Liu et al, 2017).…”
Section: Associations Of Cazymes With Other Genes Involved In Wood Sementioning
confidence: 99%